(untitled) (diségno, 2022)
The essay explores the editorial project The Situationist Times, a magazine published between 1962 and 1967 by Jacqueline de Jong, to investigate situlogy, a kind of situationist topology. In particular, the analysis aims to delve into the role of drawing and the design strategies employed to communicate this new discipline, conceived by Asger Jorn, and treated from the third to the fifth issue. Indeed, the advent of situlogy entails a radical transformation in both linguistic and compositional terms. The double pages become the setting for a labyrinthine interweaving of topological figures such as the spiral, the knot, and the ring. Encyclopedic iconographic collections allow for a morphological study that connects heterogeneous times, cultures, and disciplines. Adept at never taking a peremptory position, de Jong’s situlogical exploration is marked by openness and horizontality and invites the reader to active interpretation. In its extensive use of imagery, drawing sustains a propaedeutic and operative function: it introduces the theme and mediates between the photographic and textual documents, managing to combine mathematical patterns and decorative motifs of cultural-historical value. Finally, together with the recurrent use of manuscript text, it enables the project to preserve a confidential dimension and, likewise, to reveal the ultimate meaning of situlogy, understanding forms from their inherent potential for metamorphosis.